2022
DOI: 10.1186/s10020-022-00561-x
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow mesenchymal stem cell-derived exosomes shuttling miR-150-5p alleviates mechanical allodynia in rats by targeting NOTCH2 in microglia

Abstract: Background This study probes into the function and mechanism of bone marrow mesenchymal stem cell (BMSC)-derived exosomes loaded with miR-150-5p in mechanical allodynia. Methods BMSCs were infected with miR-150-5p inhibition lentiviruses to obtain exosomes with low miR-150-5p expression. A L5 spinal nerve ligation (SNL) model was established in rats where exosomes, NOTCH2 overexpression/inhibition plasmids, or microglial cells were intrathecally ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Intrathecal injection of MSC-EVs carrying miR-99b-3p reduced microglia activation in the spinal cord’s dorsal horn and mechanical allodynia in chronic constriction injury (CCI) rats by stimulating autophagy ( Gao et al, 2023 ). Li et al (2022) showed that the BMSC-derived exosomal miR-150-5p attenuates mechanical allodynia by targeting NOTCH2 in microglial. In addition to the beneficial action of MicroRNAs, Huc-MSCs-derived exosomes may exert analgesic effects on neuropathic pain by inhibiting activation of the TLR2/MyD88/NF-κB signaling pathway in spinal microglia ( Gao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrathecal injection of MSC-EVs carrying miR-99b-3p reduced microglia activation in the spinal cord’s dorsal horn and mechanical allodynia in chronic constriction injury (CCI) rats by stimulating autophagy ( Gao et al, 2023 ). Li et al (2022) showed that the BMSC-derived exosomal miR-150-5p attenuates mechanical allodynia by targeting NOTCH2 in microglial. In addition to the beneficial action of MicroRNAs, Huc-MSCs-derived exosomes may exert analgesic effects on neuropathic pain by inhibiting activation of the TLR2/MyD88/NF-κB signaling pathway in spinal microglia ( Gao et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Li et al documented that intrathecally administration of the bone marrow mesenchymal stem cell-derived exosomes loaded with miR-150–5p alleviate mechanical allodynia through targeting neurogenic locus notch homolog protein 2 (NOTCH2) in microglial cells following L5 spinal nerve ligation model in rat. 49 In this regard, another study showed that a single intrathecal injection of the human placental mesenchymal stem cells (hPMSCs)-derived small extracellular vesicles durably reversed mechanical hypersensitivity and neuroinflammation through miR-26a-5p/Wnt5a in mice with partial sciatic nerve ligation. 50 Histological and functional evaluation of the crushed sciatic nerve after transplanting the gel containing human multipotent mesenchymal stromal cell-derived extracellular vesicles (MSCs-EVs) showed a significant decrease in apoptotic neuronal death and an increase in regeneration-associated proteins NF-200 and GAP-43, as well as a decrease in muscle atrophy.…”
Section: Methodsmentioning
confidence: 99%
“…These include, but are not limited to: 1, dementia, such as vascular dementia. 199 HIV-associated neurocognitive disorders 200 and radiation-induced cognitive dysfunction 201,202 ; 2, functional disorders, such as epilepsy 203 and mechanical allodynia 204 ; 3, congenital abnormalities, such as spina bifida aperta 205 ; 4, neuropsychological conditions, such as depression 206 and stress 207 ; 5, brain aging [208][209][210] ; 6, iatrogenic brain problems, such as deep hypothermic circulatory arrest. 211 PLASTIC SURGERY AND SC-EXO THERAPY Wound healing occurs in all parts of the human body, with cutaneous wounds being the most common.…”
Section: Other Neurosurgical and Related Diseasesmentioning
confidence: 99%